Pengembangan Buku Ajar Evaluasi Pembelajaran Anak Usia Dini Bermuatan Nilai Karakter Tri Kaya Parisudha Dengan Strategi Think Talk Write - I Ketut Suparya; I Gede Arya Wiradnyana; Komang Agus Budhi Arya Pramana; Ni Luh Ika Windayani; Ni Wayan Risna Dewi (Jayapangus Press, 2022)
The purposes of this study are (1) to describe the feasibility of evaluating early childhood learning textbooks containing the Tri Kaya Parisudha character with a think talk write strategy developed in terms of content and construct validity, (2) to describe the feasibility of early childhood learning evaluation textbooks containing characters. Tri Kaya Parisudha with a think talk write strategy which was developed in terms of practical use in the classroom. This research is a Research and Development (R&D) model or research and development. Research and development is a process or scientific steps used in researching, producing or improving existing products. This development refers to the model of the Borg and Gall measures. The data that has been obtained using an instrument that has been designed and then analyzed descriptively with qualitative descriptive techniques. The quality of the product in the form of teaching materials developed must meet the feasibility of the aspects of validity and practicality. From the results of research data analysis, the conclusions of this study are as follows: (1) early childhood learning evaluation textbooks containing the value of the tri Kaya Parisudha character with thik talk write settings have met the feasibility of content validity with a score of 4.52 being in the very good category, (2) early childhood learning evaluation textbooks containing the value of the tri Kaya parisudha character with the thik talk write setting have met the practicality seen from the aspect of using time which is classified as efficient, and the student score of 3.72 is in the good category.